Multiple metastatic tumors in the oral cavity - Beena, VT (Medknow Publications, 2011)
Metastatic lesions to the oral region are uncommon and account for approximately 1% of all malignant oral tumors. In 25% of the cases, oral metastases are found to be the first sign of the metastatic spread; and in 23% of the cases, it is the first indication of an undiscovered malignancy at a distant site. Metastases to oral soft tissues are even less frequent than jaw bones. Because of its rarity, the clinical presentation of a metastatic lesion in the oral cavity can be deceiving, leading to a misdiagnosis of a benign process; therefore, in any case where the clinical presentation is unusual, especially in patients with a known malignant disease, a biopsy is mandatory. Here, we are presenting a rare case of multiple secondary tumors in the attached gingiva in an otherwise apparently healthy patient with no other symptoms of the primary tumor. It subsequently led to the diagnosis of Pancoast tumor (bronchoalveolar carcinoma) metastasizing simultaneously to multiple sites in the oral cavity and bilateral adrenal glands.